Analysis of full-text publication and publishing predictors of abstracts presented at an Italian public health meeting (2005–2007). (December 2015) - Castaldi, S.; Giacometti, M.; Toigo, W.; Bert, F.; Siliquini, R.
Abstract Background In Public Health, a thorough review of abstract quality evaluations and the publication history of studies presented at scientific meetings has never been conducted. To analyse the long-term outcome of quality abstracts submitted to conferences of Italian Society of Hygiene and Public Health (SItI) from 2005 to 2007, we conducted a second analysis of previously published material aiming to estimate full-text publication rate of high quality abstract presented at Italian public health meetings, and to identify predictors of full-text publication. Methods The search was undertaken through scientific databases and search engines and through the web sites of the major Italian journals of Public Health. For each publication confirmed as a full text paper, the journal name, impact factor, year of publication, gender of the first author, type of study design, characteristics of the results and sample size were collected. Results The overall publication rate of the abstracts presented is 23.5 %; most of the papers were published in Public Health journals (average impact factor: 3.007). Non universitary affiliation had resulted in a lower probability of publication, while some of the Conference topics had predisposed the studies to an increased likelihood of publication as well as poster form presentation. Conclusions The method presented in this study provides a good framework for the evaluation of the scientific evidence. The findings achieved should be taken into consideration by the Scientific Societies during the contributions selection phase, with the aim of achieving a continuous improvement of work quality. In the future, it would be interesting to survey the abstract authors to identify reasons for unpublished data.